HUBUNGAN POLA ASUH KELUARGA DENGAN RISIKO PENGGUNAAN NARKOTIKA PADA REMAJA - Sonia Meili Kamalin; Siti Rahmalia Hairani Damanik; Yufitriana Amir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The system of family care gives big influences to misuse drugs in teens. The aim of this research is to know the system of family care in misusing of drugs connected among teens in SMK Kansai Pekanbaru by correlation descriptive research and cross sectional appoach. The sample of the research is based on the inclution of criteria by using stratified random sampling technique to 81 boys. The means of measure is questionary, univariate analysize is used to know distribution frequency and bivariat the chi-square test. The result of the research is to knows the majority of teens in 15-17 age range about 61 teens (75,3%), the most of them got demokratic family care system about 32 teens (39,5%). The result of statistic test used chi-square test is found the significant relationship between the system family care and the risk of drugs for teens with the score p = 0,004.Keywords: caring, drugs, family, teens